2015
DOI: 10.7759/cureus.310
|View full text |Cite
|
Sign up to set email alerts
|

Hand Hygiene: Knowledge and Attitudes of Fourth-Year Clerkship Medical Students at Alfaisal University, College of Medicine, Riyadh, Saudi Arabia

Abstract: Introduction: Little is known about the clerkship (clinical) medical students’ knowledge of hand hygiene as the single most important precautionary measure to reduce nosocomial healthcare-associated infections. The aim of this study is to explore the knowledge of, and attitudes towards, hand hygiene practices among fourth-year clerkship medical students at Alfaisal University, College of Medicine, Riyadh, Saudi Arabia.Materials and Methods: A cross-sectional, paper-based, Yes/No formatted questionnaire was adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 23 publications
6
23
1
1
Order By: Relevance
“…Accordingly, throughout our study, it was found that students' practice of HH was affected by the performance of their role models which was comparable to the findings of Hamadah et al in which they stated that students lack proper HH practice in the absence of living examples (physicians, residents) 6 . The majority of students in a study conducted in Australia, felt that acting as role models for HH in regards to other healthcare workers was considered as their responsibility 27 .…”
supporting
confidence: 77%
See 3 more Smart Citations
“…Accordingly, throughout our study, it was found that students' practice of HH was affected by the performance of their role models which was comparable to the findings of Hamadah et al in which they stated that students lack proper HH practice in the absence of living examples (physicians, residents) 6 . The majority of students in a study conducted in Australia, felt that acting as role models for HH in regards to other healthcare workers was considered as their responsibility 27 .…”
supporting
confidence: 77%
“…One of these efforts was introduced by the WHO which was the (My five Moments for Hand Hygiene) approach. These five moments include the following: before touching a patient, the moment before performing an aseptic or clean procedure, following exposure to body fluids, after touching a patient, and after touching any of the patient surroundings 1,12. Even though frequent reports about the knowledge of HH among medical students in different countries have been found, Saudi Arabia has greatly fallen behind in this field 6 . Such studies are of great value as students fill a large number in healthcare facilities during their training phase and may contribute to the transmission of infections.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of HCAI in Saudi Arabia vary from 13% to 48 % in teaching hospitals (18,19). Despite the relative simplicity in technique of hand washing, regional studies have demonstrated poor awareness and inadequate compliance (20,21).…”
Section: Discussionmentioning
confidence: 99%